Vein of Galen Aneurysmal Malformation Presenting with Obstructive Hydrocephalus: A Case Report - Khanal, Nischal; Rajbhandari, Binod; Sedain, Gopal; Shilpakar, Sushil K (Journal of Institute of Medicine Nepal, 2019)
The prognosis for children harboring vein of Galen aneurysmal malformation (VGAM) has significantly improved over the last three decades due to refinements in the interventional endovascular techniques. It is now possible to obliterate the malformation with better results. Endovascular approaches evolved as the gold standard treatment option for this disorder. A few reports were published warning about the high rate of complications associated with ventriculoperitoneal shunting (VPS) in this setting. We present a pediatric case with VGAM where an emergency ventriculoperitoneal shunt procedure was required for symptomatic obstructive hydrocephalus (HCP) and management of the subsequent complications that followed it.